Housing and Cancer Care and Outcomes: A Systematic Review. (8th September 2022) - Fan, Qinjin; Nogueira, Leticia; Yabroff, K Robin; Hussaini, S M Qasim; Pollack, Craig E
Abstract: Background: Access to stable and affordable housing is an important social determinant of health in the United States. However, research addressing housing and cancer care, diagnosis, and outcomes has not been synthesized. Methods: We conducted a systematic review of studies examining associations of housing and cancer care and outcomes using PubMed, Embase, Scopus, and CINAHL. Included studies were conducted in the United States and published in English between 1980 and 2021. Study characteristics and key findings were abstracted and qualitatively synthesized. Results: A total of 31 studies were identified. Housing-related measures were reported at the individual level in 20 studies (65%) and area level in 11 studies (35%). Study populations and housing measures were heterogeneous. The most common housing measures were area-level housing discrimination (8 studies, 26%), individual-level housing status (8 studies, 26%), and individual-level housing concerns (7 studies, 23%). The most common cancer outcomes were screening (12 studies, 39%) and mortality (9 studies, 29%). Few studies assessed multiple dimensions of housing. Most studies found that exposure to housing insecurity was statistically significantly associated with worse cancer care (11 studies) or outcomes (10 studies). Conclusions: Housing insecurity is adversely associated with cancer care and outcomes, underscoring the importance of screening for housing needs and supporting systemic changes to advance equitable access to care. Additional research is needed to develop and test provider- and policy-level housing interventions that can effectively address the needs of individuals throughout the cancer care continuum.